(untitled) (Journal on Geoinformatics, Nepal, 2019)
Nepal has a diverse geography. The declaration of Nepal as Federal Democratic Republic Nepal has occurred recently. Transformation in administrative boundaries has undertaken. For the formulation of changes in administrative divisions, changes in different phases were involved. Committees that are formed and methods that are adapted socially, technically and administratively to map the local government units is depicted through this paper. Finally, the outcomes of restructured Nepal with its individual local level are prepared with the help of Geographic Information System.